THE IMPACT OF SOCIAL MEDIA MARKETING ON BRAND LOYALTY: THE MEDIATION EFFECT OF BRAND-VALUE CONSCIOUSNESS TOWARDS ADIDAS BRAND IN INDONESIA - Hermanus, Archie Edrick; Margaretha, Silvia; Indarini, Indarini (Manajemen dan Bisnis, 2016)
The purpose of this study is to investigate the impact of social media marketing on brand loyalty with the mediation effect of brand-value consciousness towards Adidas brand in Indonesia. The analysis method in this study is using structural equation modeling (SEM). Object of this current study is highschool students (or equal) and college students who is using social media and follow Adidas on social media, on the amount of 150 people. Data processing using softwares such as SPSS – PASW Statistics version 18 for Windows OS and IBM – AMOS version 22 for Windows OS. The results of this study indicated that social media marketing has a significant effect on brand loyalty; brand consciousness and value consciousness mediate the relationship beetwen social media marketing and brand loyalty.